Safety and immunogenicity of synchronous COVID19 and influenza vaccination - Andreina Baj; Daniela Dalla Gasperina; Daniele Focosi; Greta Forlani; Francesca Drago Ferrante; Federica Novazzi; Lorenzo Azzi; Fabrizio Maggi (Journal of Clinical Virology Plus, 2022)
Given the ongoing COVID19 pandemic, the decline in serological response since dose 2, and the upcoming flu season, COVID19 vaccines will increasingly be administered in combination with vaccines against seasonal pathogens. It is of interest to confirm that concurrent vaccination against influenzavirus has no negative impact on serological response to SARS CoV-2.Anti-Spike IgG and Anti-Receptor Binding Domain (RBD) Neutralizing Antibodies (NAb) in serum  was assessed in 64 immunocompetent healthcare workers (HCW) before and 14 days post the third dose of BNT162b2 vaccine (Comirnaty®, Pfizer/BioNTech) or BNT162b2 plus quadrivalent flu vaccine (Vaxigript Tetra ®Sanofi Pasteur) on the same day.We report here safety and efficacy of combined BNT162b2 and flu vaccine in 64 healthcare workers at a single institution. No differences were found in adverse events or anti-Spike antibody levels.